Interaction Between Internal and External Governance Mechanisms as Firm Performance Elements: an international study - San Martin Reyna, Juan Manuel (Review of Business Management, 2012)
This paper studies the influence of internal corporate governance mechanisms - ownership concentration, board of directors, and indebtedness - on firm performance, and if such mechanisms depend on institutional frameworks. Based on a sample of 765 companies from seven countries of the European Union over a four-year period (2000-2003), we found that firm performance tends to increase as ownership is concentrated, protection to investors gets stronger, and indebtedness levels decrease, as well as the size of the board of directors. Moreover, in order to analyze the joint effect of the institutional framework and the mechanism of government, we found evidence that the legal protection offered to investors in each country determines the use of internal governance mechanisms. Also, our findings show that the estimated impact of corporate governance variables on firm performance more than doubles when discretionary accruals are eliminated from measured profitability. Key words: Firm performance. Institutional framework. Legal protection. Governance mechanisms.